An Analysis of Perceived Popularity, Quality, Price, and their Relationship with Several Brands of Fried Oil - Ujang Sumarwan (Media Gizi dan Keluarga, 2000)
he purpose of this study was to identify brands of fried oil consumed by consumers, to examine consumers¡¦ perceptions of brands¡¦ popularity, quality, and price, and to analyze the relationships among perceptions of brands¡¦ popularity, quality, price, and brands¡¦ consumption. Data were collected from 150 graduate students of IPB in March 2000. The results of the study showed three brands of fried oil: Bimoli, Filma, and Tropical were most likely to be consumed by respondents. Respondents perceived Bimoli as the most popular brands, followed by Filma, and Tropical. However, majority of respondents perceived Filma as the best quality of brands, followed by Bimoli and Tropical. The majority of respondents also perceived Filma as the most expensive brands, followed by Bimoli and Sunrice. The results also showed that perceived popularity of brands was not related to brand consumption. Respondents who perceived a certain brand as the most popular were not likely to buy and to consume that brand.